2007
DOI: 10.1007/s10528-007-9086-x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased total carbonic anhydrase esterase activity and decreased levels of carbonic anhydrase 1 isozyme in erythrocytes of type II diabetic patients

Abstract: In this exploratory study, we investigated total erythrocyte carbonic anhydrase (CA) estrase activity as well as CA I isozyme concentration in patients with diabetes mellitus type II (DM) and healthy individuals of Howard University Hospital community. Total estrase activity of CA was measured spectrophotometrically using p-nitrophenol acetate before and after inhibition with acetazolamide. CA I isozyme was measured by radial immunodiffusion using monoclonal antibody (CA I) in agarose plates. The study involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…CA activity was determined as acetazolamide (AZM)-sensitive esterase activity following a standard method modified from Gambhir et al (Gambhir et al, 2007). The assay consisted of 100l of tissue homogenate in 1ml of assay medium containing 63mmoll -1…”
Section: Ca Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…CA activity was determined as acetazolamide (AZM)-sensitive esterase activity following a standard method modified from Gambhir et al (Gambhir et al, 2007). The assay consisted of 100l of tissue homogenate in 1ml of assay medium containing 63mmoll -1…”
Section: Ca Activitymentioning
confidence: 99%
“…After determining the initial slope of esterase reaction, a specific CA inhibitor, AZM (7mmoll -1 ), was added to the assay, and CA activity was determined as the difference in the initial reaction slopes before and after AZM addition using the molar extinction coefficient for p-nitrophenol of 5lmmol (Nielsen and Frieden, 1972;Smeda and Houston, 1979;Gambhir et al, 2007;Malheiro et al, 2009). CA activity determined with the AZM-sensitive esterase assay correlates with the cellular CA content (Gambhir et al, 2007). Protein concentration was measured in tissue homogenates of juvenile oysters using the Bio-Rad protein assay (Bio-Rad Laboratories, Hercules, CA, USA) using bovine serum albumin as a standard.…”
Section: Ca Activitymentioning
confidence: 99%
“…It is possible that CA activity may increase, then slowly return to normal and subsequently decrease through the steps of diabetes. Previous studies have shown that adult individuals with type 2 diabetes have significantly lower CA activity than normal individuals (Gambhir et al 2007).…”
Section: Resultsmentioning
confidence: 90%
“…Furthermore, the values varied with the severity of the diabetes or insulin resistance (Gambhir et al 2007). Kondo et al (1975) reported contradictory results, however, as they found increased levels of both CAI and CAII in patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Gambhir et al [21] observed decrease in carbonic anhydrase activity in type II diabetic patients when compared with Normal subjects. They therefore speculate that the change in the CA activity may be of fundamental importance in the regulation of intracellular; pH for the basic control of metabolism in diabetes mellitus.…”
Section: Carbonic Anhydrase Inhibition (With Acetazolamide) Increasesmentioning
confidence: 97%